(untitled) (CIPEEX, 2025)
The study investigated the phytochemical composition of the leaves of Justicia goianensis L., a species of the Acanthaceae family, widely found in the Cerrado biome of Goiás. The family is known for its medicinal properties, and the species shows pharmacological potential due to the presence of bioactive compounds. The objective was to identify and analyze the presence of secondary metabolites in the leaves of J. goianensis, which may have therapeutic applications. The leaves were collected, dried at room temperature, and pulverized. Subsequently, determinations of moisture content, total ash, and acid-insoluble ash were carried out according to the Brazilian Pharmacopoeia V. For phytochemical prospecting, adapted qualitative tests were used to detect the presence of anthraquinones, cardiac glycosides, flavonoids, saponins, tannins, and alkaloids in the samples. The analyses revealed the presence of anthraquinones, cardiac glycosides, flavonoids, saponins, and tannins in the leaves of Justicia goianensis. The total ash content was 3%, and the acid-insoluble ash content was 0.07%, demonstrating the purity of the samples. The compounds identified are known for their anti-inflammatory, antimicrobial, and anticancer properties. The presence of various bioactive secondary metabolites in the leaves of Justicia goianensis suggests great therapeutic potential, with possible applications in pharmacology. However, additional biological studies are necessary to further explore its properties and validate its medicinal use.